As práticas docentes na educação étnico-racial indígena na EEEFM Primo Bitti : análises acerca da EJA no quadriênio 2019/2022 - Mendonça, Elineide de Oliveira (2024)
With the aim of investigating the challenges and teaching practices in Youth and Adult Education (EJA) at Primo Bitti State School of Elementary and High School (EEEFM) from 2019 to 2022 regarding indigenous ethnic-racial education, this research sought to understand the material and time conditions that permeate the education of indigenous peoples living in villages who attend this mode of education, aiming to identify possible challenges and opportunities to promote a more inclusive education sensitive to their cultural particularities. To achieve this objective, we set out to investigate the trajectory that would provide us with precise and well-founded answers on the subject studied here, using as a starting point a bibliographic review enriched by our analyses at the school and direct contact with the professionals who were there during this period. All available documents at the school related to EJA during the research period were analyzed, prioritizing a qualitative data survey, as appropriate for the issues under study. With the study, we found that indigenous education at the school had a timid but courageous approach at the beginning, maintained by the team of the period, yielding good indigenous ethnic-racial relations among EJA students. These teaching practices from 2019 to 2022 were marked by an innovative and inclusive approach, with teachers implementing pedagogical strategies that valued cultural diversity, providing students with an enriching learning environment. During this period, interdisciplinary projects were developed that highlighted the history, culture, and contributions of indigenous peoples, integrating these themes into the EJA curricula. The practices included activities such as cultural events, visits to local indigenous communities, and partnerships with leaders and representatives from these communities, providing students with diverse and authentic experiences. Additionally, teachers emphasized the importance of critical reflection on ethnic-racial issues, promoting open and inclusive dialogues. These practices aimed not only to transmit knowledge but also to develop social awareness and respect for diversity, contributing to a more comprehensive and inclusive civic education